An approach to investigate coarse aggregates movement of asphalt mixture based on wheel tracking test. (22nd November 2021) - Liu, Wenchang; Lin, Hongwei; Guo, Hongyu; Zhang, Hongchao; Zhang, Shuguang; Mao, Yongqiang; Fu, Huan
Graphical abstract: Highlights: A newly-developed approach was proposed to investigate the rutting mechanism. Translation and rotation movement of coarse aggregates were discussed. The relationships between aggregate movement and rutting development were revealed. Abstract: Rutting is a critical pavement failure factor that affects the service life of asphalt mixtures. During the permanent deformation of the asphalt mixture, the aggregates shift and rotate, which significantly affects the deformation process. In this study, the microstructural changes in asphalt mixtures before and after the wheel tracking test (WTT) is performed is investigated using X-ray computed tomography (CT). An aggregate tracking method based on CT is proposed to monitor the spatial motion of coarse aggregates in the WTT. The results show that the average displacement of coarse aggregates can be used to accurately predict variations in the rutting depth. The downward deformation of the specimens is primarily caused by the downward movement of the aggregates, whereas their bulge deformation is caused by the upward and transverse movements of the aggregates. The relative displacement of the aggregates can accurately describe the variations in the compaction and loosening zones in the specimens during the WTT. In addition, as the loading time progresses, the variation amplitude of the aggregate angle decreases gradually, before finally approaching a small angle. The aggregate angle generally exhibits a flat state arrangement along the loading tracks. The experimental results provide a solid foundation for further investigating the rutting mechanism and improving the rutting resistance of asphalt mixtures.